Larval Diet Abundance Influences Size and Composition of the Midgut Microbiota of Aedes aegypti Mosquitoes - MacLeod, Hannah J.; Dimopoulos, George; Short, Sarah M. (Frontiers in Microbiology, 2021)
The midgut microbiota of the yellow fever mosquito Aedes aegypti impacts pathogen susceptibility and transmission by this important vector species. However, factors influencing the composition and size of the microbiome in mosquitoes are poorly understood. We investigated the impact of larval diet abundance during development on the composition and size of the larval and adult microbiota by rearing Aedes aegypti under four larval food regimens, ranging from nutrient deprivation to nutrient excess. We assessed the persistent impacts of larval diet availability on the microbiota of the larval breeding water, larval mosquitoes, and adult mosquitoes under sugar and blood fed conditions using qPCR and high-throughput 16S amplicon sequencing to determine bacterial load and microbiota composition. Bacterial loads in breeding water increased with increasing larval diet. Larvae reared with the lowest diet abundance had significantly fewer bacteria than larvae from two higher diet treatments, but not from the highest diet abundance. Adults from the lowest diet abundance treatment had significantly fewer bacteria in their midguts compared to all higher diet abundance treatments. Larval diet amount also had a significant impact on microbiota composition, primarily within larval breeding water and larvae. Increasing diet correlated with increased relative levels of Enterobacteriaceae and Flavobacteriaceae and decreased relative levels of Sphingomonadaceae. Multiple individual OTUs were significantly impacted by diet including one mapping to the genus Cedecea, which increased with higher diet amounts. This was consistent across all sample types, including sugar fed and blood fed adults. Taken together, these data suggest that availability of diet during development can cause lasting shifts in the size and composition of the microbiota in the disease vector Aedes aegypti.